Protecting cross border online purchasers: analysis of Malaysian law / Siti Nurlina Mohd Sallehhudin ... [et al.] - Mohd Sallehhudin, Siti Nurlina; Megat Yahya, Megat Mohd Shauqi; Othman, Wan Nashitah; Muhammad Salehuddin, Nur Ainaa (2013)
The aim of this research is to develop a set of recommendations to protect cross border online purchasers who purchased goods from vendors in Malaysia. This research is motivated by the fact that cross border online purchasers are still vulnerable due to lack of special protection accorded to them. This research deals with five main issues commonly faced by cross-border online purchasers i.e. non-delivery of goods, late delivery of goods, goods that are unfit for a particular purpose, goods which are of non-merchantable quality and misleading of advertisement. Being a legal research, the methodology used in this research is purely qualitative , whereby primary legal sources such as statutes and case laws have been collected for the purpose of answering the two-tier research questions. This research analyses the relevant laws in Malaysia such as Contracts Act 1950, Electronic Commerce Act 2006, Consumer Protection Act 1999 and Sales of Goods Act 1957. In addition, this research also looks into the law of other countries i.e. the United States and the European Union. The findings from the legal and case analysis have been used as an input to develop a set of recommendations to protect cross border online purchasers who purchased goods from vendors in Malaysia. The recommendations contain both the substantive and procedural aspects of the law that can be used as a reference to develop a legal protection mechanism for cross-border online purchasers who purchased goods from vendors in Malaysia.